Weed abundance is positively correlated with native plant diversity in grasslands of southern Australia - Martín-Forés, Irene (PLoS One, 2017)
Weeds are commonly considered a threat to biodiversity, yet interactions between native and exotic species in grasslands are poorly understood and reported results vary depending on the spatial scale of study, the factors controlled for and the response variables analysed. We tested whether weed presence and abundance is related to declines in biodiversity in Australian grasslands. We employed existing field data from 241 plots along a disturbance gradient and correlated species richness, cover and Shannon diversity for natives and exotics, controlling for seasonal rainfall, climatic gradients and nutrient status. We found no negative relationships in terms of emergent diversity metrics and occupation of space, indeed, many positive relationships were revealed. When split by land-use, differences were found along the disturbance gradient. In high-moderately disturbed grasslands associated with land-uses such as cropping and modified pastures, positive associations were enhanced. Tolerance and facilitation mechanisms may be involved, such as complementary roles through different life history strategies: the exotic flora was dominated mainly by annual grasses and herbs whereas the native flora represented more diverse growth-forms with a higher proportion of perennials. The positive relationships existing between native and exotic plant species in high-moderately disturbed grasslands of South Australia are most likely due to facilitation through different strategies in occupation of space given that the effect of habitat suitability was controlled for by including environmental and disturbance factors. Consequently, although particular weeds may negatively impact biodiversity, this cannot be generalised and management focusing on general weed eradication in grasslands might be ineffectual.